ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN PERTANIAN DI KABUPATEN SLEMAN TAHUN 1998-2017 - Umi Rosidah; Hadi Sasana; Gentur Jalunggono (DINAMIC : Directory Journal of Economic, 2020)
The conversion of agricultural land is a change in the function of agricultural land intonon-agricultural land. The many functions of agricultural land are caused by several factorsincluding the increasing number of population, the number of industries and the increase inPDRB. This is not comparable with the availability of land which tends to remain in number.The purpose of this study was to determine how much influence the population, the number ofindustries and the PDRB level of conversion of agricultural land in Sleman Regency in 1998-2017. The data used in this study are secondary data and are quantitative research. With dataanalysis techniques using multiple linear regression analysis with the smallest quadrant OLS(Ordinary Least Square). The results of data analysis showed that the variable population,number of industries and PDRB had a positive and significant influence on the conversion ofagricultural land in Sleman Regency from 1998 to 2017.